2006
DOI: 10.1007/s10452-006-9062-2
|View full text |Cite
|
Sign up to set email alerts
|

The induction of diapause in Moina by species-specific chemical cues

Abstract: The ability to change the reproduction mode and produce diapausing eggs, which is prevalent in many zooplankton species, significantly impacts on the evolution and ecology of aquatic communities. The production of diapausing eggs is controlled by multiple effects of biotic and abiotic factors, including infochemicals. We have investigated the effects of chemicals exuded by conspecifics and ecologically close competing congers, Moina brachiata and M. macrocopa, which coexist in the same water body, and by large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although predation apparently does not induce a shift from parthenogenesis to sexual reproduction in M. micrura , other biotic factors may have an important role for particular Moina species. For example, high concentrations of conspecific chemical cues switch the reproductive mode of Moina macrocopa (Straus) and Moina brachiata Jurine (Zadereev & Lopatina, 2007). Male and female neonates in a single clutch, as we observed in this study, seem not so common but have been previously observed for M. micrura (Martínez‐Jerónimo, Rodriguez‐Estrada & Villasenor‐Cordova, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although predation apparently does not induce a shift from parthenogenesis to sexual reproduction in M. micrura , other biotic factors may have an important role for particular Moina species. For example, high concentrations of conspecific chemical cues switch the reproductive mode of Moina macrocopa (Straus) and Moina brachiata Jurine (Zadereev & Lopatina, 2007). Male and female neonates in a single clutch, as we observed in this study, seem not so common but have been previously observed for M. micrura (Martínez‐Jerónimo, Rodriguez‐Estrada & Villasenor‐Cordova, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on understanding these signals in temperate aquatic ecosystems (reviewed in Radzikowski, 2013) and both light and temperature continue to be considered the most important proximate stimuli triggering both the induction and termination of diapause (Stross, 1966;Hairston et al, 1990Hairston et al, , 2000Vandekerkhove et al, 2005b). However, more recently, the relevance of other factors has been pointed out, including: food shortage (Alekseev and Lampert, 2001), predation cues (Pijanowska and Stolpe, 1996), and crowding (Zadereev and Lopatina, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In species whose resting eggs are sexually produced, crowding increases the chances of female and male encounters and thus elevates the production of resting eggs (Wood, 1932). Crowding can also elevate the concentrations of conspecific or competitor exudates, metabolites and excretory substances in the water column (Hobaek & Larsson, 1990; Ban & Minoda, 1994), which promotes resting egg production through the suppression of parthenogenetic reproductive output (Zadereev & Lopatina, 2007) or inhibition of feeding (Lürling et al ., 2003). Strickler & Twombly (1975) forwarded a different perspective, in which they highlighted the possibility that freshwater cyclopoids enter diapause in response to elevated invertebrate predation.…”
Section: Seasonal Vertical Migration Of Zooplanktonmentioning
confidence: 99%